Comparison of deuterium retention in tungsten exposed to deuterium plasma and gas. (August 2020) - Ye, Xiaoqiu; Wang, Wei; Pan, Qifa; Jiang, Chunli; Wang, Yifang; Chen, Xiaohong; Wu, Jiliang; Chen, Changan
Highlights: D retention in plasma exposure W is much higher than that of gas charging W. D2 desorption temperature of plasma exposure W is lower than that of gas charging W. Detrapping energy of D in gas charging W is 2.17 eV. Detrapping energy of D in plasma exposure W is 1.04 eV. Abstract: Deuterium (D) retention behavior in tungsten (W) exposed to D plasma and D2 gas was studied by means of thermal desorption spectroscopy (TDS): D plasma exposure in which W was exposed to D plasma with 35 eV/D + at 393 K for 0.5 h to the fluence of 3.8 × 10 24  D/m 2 ; D2 gas charging in which W was exposed to D2 gas of 500 kPa at 773 K for 4 h. TDS shows that the total D retention in plasma exposure W is ~10 22  D/m 2, two orders of magnitude higher than that of gas charging W; however, the D2 desorption peak of gas charging W is 952 K, much higher than 691 K of plasma exposure W at the heating rate of 20 K/min. The detrapping energies of deuterium were determined experimentally from the measured peak temperatures at different heating rates and were found to be 2.17 eV for the gas charging W and 1.04 eV for the plasma exposure W, respectively.